1999
DOI: 10.1097/00001756-199903170-00004
|View full text |Cite
|
Sign up to set email alerts
|

Complete mutism after midbrain periaqueductal gray lesion

Abstract: Several neurophysiological studies have highlighted the role of the midbrain periaqueductal gray matter (PAG) in the initiation of vocalization in various animal species, from frogs to primates. With regard to humans, only two cases of complete mutism following a lesion to the PAG have been reported so far. This article describes a new case of a patient (GM) who, following an ischemic lesion to the periaqueductal gray region of the midbrain, presented with complete and irreversible mutism, though her language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…Finally, the PAG has a distinctive role in vocalizations, specifically call initiation (Jürgens, 2002). The PAG is active during speech in humans (Schulz et al, 2005), and lesions of the PAG can lead to mutism (Esposito et al, 1999).…”
Section: Periaqueductal Gray/central Gray (Pag/cg) Mammalsmentioning
confidence: 99%
“…Finally, the PAG has a distinctive role in vocalizations, specifically call initiation (Jürgens, 2002). The PAG is active during speech in humans (Schulz et al, 2005), and lesions of the PAG can lead to mutism (Esposito et al, 1999).…”
Section: Periaqueductal Gray/central Gray (Pag/cg) Mammalsmentioning
confidence: 99%
“…Stimulation of this region produces vocalisation (Jürgens and Ploog, 1970;Suga et al, 1973;Waldbillig, 1975;Yajima et al, 1980;Lu and Jürgens, 1993), whilst its lesion produces mutism (Adametz and O'Leary, 1959;Jürgens and Pratt, 1979;Esposito et al, 1999). Anatomical observations in the cat showed that neurons in the latero-caudal periaqueductal grey project bilaterally to the nucleus retroambiguus in the caudal medulla oblongata, which in turn projects to motor neurons innervating structures involved in vocalisation e e.g.…”
Section: Periaqueductal Greymentioning
confidence: 99%
“…Lesions to the face motor cortex in chimpanzees and other non-human primates do not affect their ability to produce vocalizations (Kuypers 1958b;Jurgens et al 1982;Kirzinger and Jurgens 1982). Lesions to avian nXIIts and DM and mammalian Am and PAG result in muteness in both vocal learners and non-learners (Brown 1965;Nottebohm et al 1976;Seller 1981;Jurgens 1994Jurgens , 1998Esposito et al 1999). …”
Section: Functions Of Vocal Brain Areas In Birds and Humansmentioning
confidence: 99%